Insights into the involvement of long non-coding RNAs in doxorubicin resistance of cancer - Zhang, Hai-Bo; Hu, Yang; Deng, Jun-Li; Fang, Guo-Ying; Zeng, Ying (Frontiers in Pharmacology, 2023)
Doxorubicin is one of the most classical chemotherapeutic drugs for the treatment of cancer. However, resistance to the cytotoxic effects of doxorubicin in tumor cells remains a major obstacle. Aberrant expression of long non-coding RNAs (lncRNAs) has been associated with tumorigenesis and development via regulation of chromatin remodeling, transcription, and post-transcriptional processing. Emerging studies have also revealed that dysregulation of lncRNAs mediates the development of drug resistance through multiple molecules and pathways. In this review, we focus on the role and mechanism of lncRNAs in the progress of doxorubicin resistance in various cancers, which mainly include cellular drug transport, cell cycle disorder, anti-apoptosis, epithelial-mesenchymal transition, cancer stem cells, autophagy, tumor microenvironment, metabolic reprogramming and signaling pathways. This review is aimed to provide potential therapeutic targets for future cancer therapy, especially for the reversal of chemoresistance.